1992
DOI: 10.1037/0022-006x.60.3.450
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of three family therapy programs for treating family conflicts in adolescents with attention-deficit hyperactivity disorder.

Abstract: Sixty-one 12- to 18-year-olds were randomized to 8-10 sessions of behavior management training (n = 20), problem-solving and communication training (n = 21), or structural family therapy (n = 20). Families were assessed at pre- and posttreatment and 3-month follow-up. All treatments resulted in significant reductions in negative communication, conflicts, and anger during conflicts and improved ratings of school adjustment, reduced internalizing and externalizing symptoms, and decreased maternal depressive symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
102
3
6

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 258 publications
(113 citation statements)
references
References 49 publications
2
102
3
6
Order By: Relevance
“…Mothers showing less than normal values on the DFI subscale monitoring increased their monitoring after 3 months of treatment. Several studies have shown that a child with ADHD elicits more controlling behaviour from adults (Barkley et al, 1991;Barkley et al, 1992;Johnston, 1996;Johnston, & Mash, 2001). The mothers with a high degree of influence or control according to the DFI subscale showed a greater reduction of this behavior compared to mothers with normal levels of influence or control according to DFI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mothers showing less than normal values on the DFI subscale monitoring increased their monitoring after 3 months of treatment. Several studies have shown that a child with ADHD elicits more controlling behaviour from adults (Barkley et al, 1991;Barkley et al, 1992;Johnston, 1996;Johnston, & Mash, 2001). The mothers with a high degree of influence or control according to the DFI subscale showed a greater reduction of this behavior compared to mothers with normal levels of influence or control according to DFI.…”
Section: Discussionmentioning
confidence: 99%
“…Parents of children with ADHD have been found to be more directive and commanding, show more disapproval, give fewer rewards and show a more negative behavior towards their child compared to parents of control families (Barkley, Fischer, Edelbrock, & Smallish, 1991;Barkley, Guevremont, Anastopoulos, & Fletcher, 1992;Johnston, 1996;Johnston & Mash, 2001). Both medication and behavioural treatment of the child may be effective in reducing aspects of family stress (Johnston, & Mash, 2001;Wells et al, 2000).…”
mentioning
confidence: 99%
“…In cases of attentional and overactivity problems, effective family therapy focuses on helping families to develop patterns of organization conducive to effective child management (Barkley et al, 1992). Such patterns of organization include a high level of parental co-operation in problem-solving and child management; a clear intergenerational Parent training, as described in the previous section on oppositional behavioural problems, focuses on helping parents develop the skills to monitor specific positive and negative behaviour and to modify these by altering those interactions and events that occur before and after them (e.g.…”
Section: Attentional and Overactivity Problemsmentioning
confidence: 99%
“…Simons & Thase (1992), 53 patients with major depression, Age of onset of first depression, No Barkley et al(1992), 61 adolescents with ADHD, Age of ADHD onset, No Mulhern et al(1992), 49 long-term survivors of childhood leukemia,Age at diagnosis Age at testing, No Wieczorek & Miller (1992), 156 convicted-while-intoxicated offenders, Age at first drink, No Killen et al (1992) (1996), 516 smoking cessation participants, Age of onset of smoking. Number of lifetime quit attempts., No Pianta et al (1996), 110 women in second trimester of pregnancy, Number of T ≥ 65 elevations range: 0 (44%) to 7 (5%), No Newman et al (1996) Grilo et al (1997), 114 adolescent Psychiatric inpatients, Age at first psychiatric contact & psychiatric hospitalization; number of prior psychiatric hospitalizations, No Agras et al (1997), 93 obese women, Age of onset of being overweight and age of onset of binge eating, No…”
Section: Appendix Five-year Systematic Reviewmentioning
confidence: 99%